Anatomy of the scape in hypolytreae species (mapanioideae, cyperaceae): comparative analysis and phylogenetic implications - Kanofre, Ellen Beatriz Santos; Monteiro, Mariana Maciel (Revista brasileira de botânica, 2025)
Cyperaceae comprise one of the most species-rich families among monocot, with genera resolved into two subfamilies: Cyperoideae and Mapanioideae. While Cyperoideae encompasses ca. 84 genera, Mapanioidae is composed of only 11 genera, five of which are monotypic, resolved into two monophyletic tribes: Hypolytreae and Chrysitrichae. The low number of Mapanioideae genera seems to be proportional to the few studies involving the family, especially concerning anatomical characters, which hampers the access to homologies, as well as the resolution of the phylogenetic and taxonomic relationships within the subfamily. Thus, this work aimed to investigate anatomical traits of the scape of species of Diplasia , Hypolytrum , Mapania and Scirpodendron , to verify phylogenetically informative features for Mapanioideae relationships. The species exhibit differences regarding the the shape of the scape, presence of trichomes and papillae, distribution of the aerenchyma and arrangement of the vascular bundles. While most anatomical characters showed high plasticity related to the environmental and developmental stimuli, it is significant that vascularization traits, such as the type and arrangement of vascular bundle in the scape, were conservative at higher taxonomic levels. Based on the observed morphological features, these characters reinforce the phylogenetic relationship of Mapania and Scirpodendron as sister groups, the taxonomic boundary between Mapania and Hypolytrum and raise questions towards the resolution of Diplasia within Hypolytreae. Therefore, the scape anatomy is a potential source of information to phylogenetic relationships obtained exclusively through molecular data, contributing to the understanding of the evolutionary history of restricted and overlooked groups, such as Mapanioideae.